Plan de Desarrollo y Compromiso Social de la Empresa Pública Municipal de Saneamiento y Ambiental de Babahoyo (EMSABA EP) - Leonor Karina Pinela Vera, Leonor Karina Pinela Vera (2017)
The current study in the economic index, quality of service and population development have allowed the inhabitants to increase productivity and tourism activity in order to offer their children a good living and improvement of the quality of life. Hence the planning and commitment of the public sector to implement new strategies and construction of works that guarantee an equitable development, competent for its constituents. Considering that one of the principles is the quality of life in education, recreation spaces, health and, above all, basic services for all sectors, whether urban or rural. This is why, according to the studies carried out and the main objectives of the Good Living Plan, it has been decided to carry out a design for the supply of drinking water, sewerage and flood control in rural areas, which entails citizens having access to this quality service. The case study carried out is a Development and Social Commitment Plan of the Municipal Public Company of Sanitation and Environmental of Babahoyo (EMSABA EP), which the municipality has as objective the amplitude of the service and to develop a system of potable water, sewerage and flood control in the parishes of La Union, Febres-Cordero, Caracol and Pimocha; as well as the infrastructure for customer service. The execution of the case study was carried out at the beginning of the month of March in the period 2017 through a work plan, beginning with the investigation of the technical - commercial department of the company knowing what the main problems of the community would be, the connections that use and sewer system, knowledge of the development plan and commitment for affected parishes, funding, functionalities and departments involved; in addition to the control and evaluation of planning